The impact of accounting and auditing ethics in reducing fraud and manipulation in the financial statements of commercial banks - A field study of Ashti Bank in Sulaymaniyah Governorate - Sheelan Arif Ahmed; Rizgar Ali Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The research discussed the role of the ethics of the accounting and auditing profession and their impact on the development of internal audit and reducing the manipulation of financial statements in the Kurdistan Region of Iraq, and reduce accounting practices that affect the decisions of users of those financial statements, through the development of the role of the accountant and ensure its integrity and objectivity in the preparation of financial statements and in a manner that enhances Trust of the beneficiaries of accounting information. The research problem was to identify the impact of the ethics of the accounting profession on the work of accountants and auditors by following a set of professional ethical principles and their impact on the development of the audit profession from the point of view of accountants and auditors and the extent of commitment of accountants and auditors to the ethics of accounting and behavioral rules for that profession. The research sought to demonstrate the impact of the commitment of accountants and auditors to the ethics of the profession of accounting and auditing in reducing the manipulation of financial statements and know the importance of qualifying accountants and auditors with ethical rules of conduct, and the impact on enhancing confidence in the profession by users of financial information. The researcher selected a sample in Ashti Commercial Bank / Sulaymaniyah governorate. The researchers used the questionnaire to collect and process data using SPSS statistical program to analyze it and get the results. The results of the statistical analysis showed that there is a strong correlation between two variables. The research has concluded that the failure of the accountant and the auditor to comply with the ethics of the accounting profession has a significant impact on the information that appears in the financial statements, which makes the adoption of principles and rules of professional conduct is necessary in the institutions and for the banks.